The Saudi family’s use of smart applications to plan its affairs and its impact on the quality of family and social interaction in the year 2021-2022 - Zakour, Rasha Saud (Journal of Humanities & Social Sciences, 2023)
The study aims to identify the family’s use of smart applications to plan its affairs and its impact on the quality of family and social interaction using the descriptive analytical method and a questionnaire designed as a study tool for a sample of (556) Saudi families. The results showed; there is a positive correlation between planning /the quality of family and social interaction at (0.05). There is no correlation between planning and (age /monthly income). There is a correlation with (educational level - number of family members) at (0.05). There is a positive correlation between the quality of family/ social interaction and the educational level at (0.05). There is no correlation with (age - monthly income - number of family members). There are differences in the browsing rate / the quality of applications with the family planning questionnaire at (0.05) due to the daily browsing rate, while there are no differences due to the quality of smart applications. There are differences in the browsing rate and the quality of applications with the family and social interaction quality questionnaire at (0.05) due to the monthly browsing rate. There are no differences due to the type of smart applications. The study recommends designing a comprehensive family application for better planning in different life affairs, The need to use smart applications by families that will be benefit to them in planning their fields of life.